Studies of Biochemical Parameters of Milk of Sheep Milked by Machine During Early Lactation Period - CETIN, M.; CIMEN, M.; DILMAC, M.; KARAALP, M. (Asian Journal of Chemistry, 2010)
In this research, it was investigated the effect of weeks on milk biochemical parameters such as fat and protein of machine milked non-dairy sheep and to show the curves of these biochemical parameters during early lactation weeks. In the study, 14 Karayaka sheep with single lamb were used. The experiment began at 4 d of lamb age and lasted after 7 weeks. Sheep were fed a diet containing 135.1 g crude protein and 9.7 M metabolisable energy (ME)/kg. The weekly means of protein were similar (except first week) to those shown for the overall early lactation. The fat of milk was secreted at its highest rate at the start of lactation and then declined until 3rd week when it started to gradually increase again until the end of the study. The fat and protein reached their lowest points at week 3, which coincided with maximum milk yield. The lactation curves of non dairy sheep milked by machine of this study were similar with reported results for dairy and non-dairy ewes.